Evaluation of Intraocular Pressure (IOP) Regarding Circadian Rhythm, Age, Sex and Eye Side in Awassi Sheep - Kulualp, K.; Kilic, S.; Cakir, S.; Orhan, C. (Hellenic Veterinary Medical Soc, 2018)
Measurement of intraocular pressure (IOP) in domestic animals has become a part of routine eye examination with advent of applanation tonometer. Delayed control of high IOP may lead to permanent blindness due to retinal ganglion cells dysfunction and optic nerve degeneration. This study aimed at evaluating IOP of Awassi sheep with respect to circadian rhythm, age, sex and eye sides and finally to establish a reference (baseline, normal) IOP value for this particular species. A total of 24 healthy sheep with different ages and sexes were used. The animals were divided into 2 equal groups, <1 (6 male, 6 female, n = 12) and >= 1 (6 male, 6 female, n = 12) years old. IOP measurements were performed twice, in the morning (6:00 a.m.) and in the evening (8:00 p.m.) with Tono-pen Vet (R) applanation tonometer. Mean LOP in the animals decreased from 16.21 mmHg in the morning to 12.65 mmHg in the evening with an approximately rate of 22% (P <0.0001). Comparison of mean LOP values of right eyes (n=12) to the left (n=12). male (n=48) to female (n-48), and ages < 1 (n=48) to >= 1 (n=48) showed no difference (P >0.05). The reference IOP for this animal was calculated as 14.43 +/- 2.72 mmHg notwithstanding any variable. It was concluded that in this breed IOP values can vary significantly as far as circadian rhythm is concerned and Tono-pen Vet (R) can be used for sheep IOP measurement as an alternative to other applanation tonometry.
Keywords: Age; Awassi Sheep; Circadian Rhythm; IOP; Tono-pen Vet (R)